Exploration of Inner Resources in Religious Experience - Festa, Yumpi Rahmanawati; Subandi, M A; Khilmiyah, Akif (The international journal of religion and spirituality in society, 2022)
A family with an autistic child undergoes significant stress and hardship. Stories from family caregivers can add to the depth of knowledge about practicing Islamic teachings beneficial to stress management. This study aimed to explore how Muslim family caregivers were aware of the inner resources gained from their religious experiences and therefore defined themselves as meaningful individuals instead of suffering ones. Using the phenomenological approach, this study involved seven family caregivers as the subjects. The stress of caring for autistic children disrupted the mental health of these family caregivers, but the stress motivated them to turn more toward Islamic teachings to build mental strength. This process signifies that the inner resources developed from religious experiences are an enlightening reappraisal of using the perspective of Allah as embodied in His teachings. This study resulted in an understanding of how religious experiences internalized into their lives can develop inner resources. The findings of this study can be used in interventions to strengthen Muslim families in dealing with the stress of caring for their autistic children.